2022
DOI: 10.1002/adpr.202200252
|View full text |Cite
|
Sign up to set email alerts
|

Cost‐Effective and Robust Multispectral Light‐Emitting Diode Device for the Readout of Plasmonic Microarray Sensors

Abstract: Localized surface plasmon resonance (LSPR) is a phenomenon known for more than 100 years, which arises from the interaction of light with metallic nanoparticles. In recent years, the field of LSPR sensing has become increasingly important in bioanalytics. Herein, a simple and robust device setup to perform time‐resolved LSPR measurements with inexpensive array sensor chips is presented. For this purpose, gold nanoparticles are spotted onto glass substrates under different conditions (droplet size/number, tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Here we used a custom-built LSPR device for the detection of an antimicrobial resistance gene, blaSHV. To the best of our knowledge, this was the first report of an LSPR-based method with a low-cost and easy-to-fabricate sensor, even in microarray scale, [23,54] of immobilized spherical AuNPs that can detect SNPs in flow-through measurements and also enables the analysis of binding kinetic parameters. Varying the analyte sequence length revealed that shorter sequences result in larger LSPR shifts, as well as faster association rates as compared to longer sequences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here we used a custom-built LSPR device for the detection of an antimicrobial resistance gene, blaSHV. To the best of our knowledge, this was the first report of an LSPR-based method with a low-cost and easy-to-fabricate sensor, even in microarray scale, [23,54] of immobilized spherical AuNPs that can detect SNPs in flow-through measurements and also enables the analysis of binding kinetic parameters. Varying the analyte sequence length revealed that shorter sequences result in larger LSPR shifts, as well as faster association rates as compared to longer sequences.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, sensors used for these measurements are usually based on lithographically fabricated chips. [ 52 ] To the best of our knowledge, this is the first report of an LSPR‐based method with a low‐cost and easy‐to‐fabricate sensor, even in microarray scale, [ 23,54 ] of immobilized chemically synthesized spherical gold NPs that can meet all above‐stated requirements.…”
Section: Introductionmentioning
confidence: 99%